Targeted Quantification of Tear Lactate and Nitric Oxide for Early Field Detection of Bovine Ocular Thelaziasis - Hamad, Weam Abbas (American Journal of Biomedicine and Pharmacy, 2026)
Background: Bovine ocular thelaziasis is characterized by conjunctival irritation, lacrimation, and inflammatory changes caused by Thelazia spp. Early detection is often challenging when worms are not yet visible. Tear metabolite alterations associated with local tissue stress and inflammation may provide a rapid, low-cost diagnostic alternative. Aim: This study evaluated tear lactate and nitric oxide (NO) levels as inexpensive metabolic indicators for early detection of bovine ocular thelaziasis. Methods: A total of 90 cattle were examined and divided into three groups (n = 30 each): confirmed thelaziasis (worm-positive), suspected early cases (clinical signs without visible worms), and healthy controls. Tear samples were collected using Schirmer strips. Lactate concentrations were measured using a colorimetric lactate assay (450 nm), while nitric oxide levels were estimated via nitrite quantification using the Griess reaction (540 nm). Data were analyzed using one-way ANOVA followed by Tukey’s post hoc test. Diagnostic performance was evaluated using ROC curve analysis. Results: Tear lactate and nitric oxide levels were significantly elevated in cattle with ocular thelaziasis compared with healthy controls. Mean lactate concentrations were 6.42 ± 1.18 mmol/L in confirmed cases, 4.87 ± 0.96 mmol/L in early suspected cases, and 2.11 ± 0.64 mmol/L in controls, showing a highly significant difference among groups (F = 98.37, P < 0.001). Similarly, nitric oxide levels were markedly increased in confirmed (38.5 ± 6.7 µmol/L) and early cases (27.3 ± 5.2 µmol/L) compared with controls (11.4 ± 3.1 µmol/L) (F = 121.52, P < 0.001). Post hoc analysis demonstrated significant differences between all groups for both metabolites (P < 0.01). Receiver operating characteristic analysis revealed strong diagnostic performance, with an area under the curve (AUC) of 0.91 for lactate and 0.94 for nitric oxide, while the combined biomarker model improved discrimination (AUC = 0.97). Using optimized cutoffs, lactate (>3.5 mmol/L) achieved 86.7% sensitivity and 83.3% specificity, nitric oxide (>18 µmol/L) achieved 90.0% sensitivity and 86.7% specificity, and their combination increased sensitivity and specificity to 93.3% and 90.0%, respectively. Conclusion: Tear lactate and nitric oxide levels were significantly elevated in early and confirmed bovine ocular thelaziasis. Their combined measurement provides a rapid, inexpensive, and non-invasive metabolic screening tool suitable for field conditions.